Edible coating utilization the chitosan base to improve melon shelf life minimally processed - Chevalier, Raquel Costa; Alves da Silva, Gisele Fernanda [UNESP]; Silva, Denize Marques da; Pizato, Sandriane; Cortez-Vega, William Renzo (Federal Inst Amapa, Campus Macapa-ifap, 2016)
Edible coatings may contribute to extend the shelf life of fresh-cut fruits by reducing moisture and solute migration, gas exchange, respiration, and oxidative reaction rates, as well as by reducing physiological disorders. The objective of this study was to evaluate the effects of chitosan application associated with montmorillonite clay and essential oil of cloves in relation to chemical, physical, microbiological (Escherichia coli, Salmonella and Yeast and Mold) and sensory attributes characteristics of melon (Cucumis melo L.) minimally processed when stored at 4 +/- 1 degrees C. The melons were washed, peeled, seeds removed, diced, was applied coatings and then the cubes were stored in a PET (polyethylene terephthalate) packaging for a period of 7 days at 4 +/- 1 degrees C. Analyses of pH, total soluble solids, titratable acidity, microbiological (Escherichia coli, Salmonella, Molds and Yeasts) and sensory analysis (texture, color, aroma and overall assessment) were carried out. The analyses were performed in triplicate on the processing day (day 0) of the samples and after 1, 3, 5 and 7 days of storage. It can be concluded that the that coatings containing chitosan together with Montmorillonite clay and essential oil of clove (T3 and T4) were more efficient in conserving the physical and chemical characteristics of minimally processed melon when compared to the control sample and treatment contained only chitosan. The use of chitosan alone and together with montmorillonite and Clove essential oil were effective in maintaining the sensory and microbiological characteristics for a longer time.
Keywords: Edible coating; Melon; Montmorillonite; Essential oil